Sweet Lupine as an Alternative Food-Feed Crop in the Mixed Systems - International Livestock Research Institute (International Food Policy Research Institute, 2020)
Dual purpose crops that meet the demands of smallholders for food and feed have a higher likelihood of being adopted by farmers. Africa RISING project in the Ethiopian highlands in collaboration with Amhara Agricultural Research Institute has evaluated sweet lupine as an alternative dual-purpose crop which can serve as a source of food for humans and feed for livestock. As a legume crop, the grain contains high level of protein (above 35%), with minimum level of alkaloid content, as opposed to the local lupine variety grown in the North western part of the country. When harvested green, the forage contains up to 20% crude protein. This dataset includes the performance of two sweet lupine varieties (Vitabor and Sanabor) evaluated at different planting space (seed rate) in the Africa RISING sites.